2021
DOI: 10.1002/hsr2.362
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among undergraduate university students during COVID‐19 movement control order in Sarawak

Abstract: Background and Aims This study aimed to examine the quality of life (QoL) and health satisfaction of undergraduate university students in Sarawak during MCO and its association with socio‐demographic profiles. Methods In this cross‐sectional study, QoL and satisfaction of health of 503 undergraduate university students (63.4% females) from a public university was assessed online using the World Health Organization QoL (WHOQOL)‐BREF instrument. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…According to Ref. [18], students staying outside the campus showed higher life satisfaction than those who were confined to the house or hostel. The freedom and flexibility of having to engage with many activities during the lockdown explained why students staying outside the campus house are more satisfied with their lives.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ref. [18], students staying outside the campus showed higher life satisfaction than those who were confined to the house or hostel. The freedom and flexibility of having to engage with many activities during the lockdown explained why students staying outside the campus house are more satisfied with their lives.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are supported with the study of Malaysia, where respondents' WHOQOL-BREF scores were high in domain of social relation (69.4±18.08), followed by environmental health (66.4±15.00), physical health (65.3±14.18) and psychological health (59.5±15.90). [15] In contrast, a study finding of Hong Kong revealed that higher mean score was found on physical health (14.07±2.63) then social relationships (12.90±2.54), psychological health (12.72±2.87), and the environment health (12.24±2.81) among women during the COVID-19 Pandemic. [17] Similarly, mean score of physical domain was higher also among general people of Hong Kong.…”
Section: Discussionmentioning
confidence: 97%
“…This finding was supported with the study of Malaysia where the respondents had overall QOL and satisfaction with health score were 3.7±0.87 and 3.9±0.82, respectively. [15] In India, (n=305), mean score of the Brunnsviken brief quality of life scale (BBQ, 12 item) was 33.91±10.158 among adult people above 18 years. [2] A contrast finding revealed in a study of China where the majority of respondents (93.8%) had a perfect score of "1.000" for QOL (EQ-5D).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the pandemic was initially announced, the Malaysian government introduced a movement control order (MCO) that closed state borders, brought economic activities to a standstill, and stopped lectures in all academic institutions. Imposition of the MCO stranded several thousands of students who were unable to return home as they could not leave their residential colleges (Cheah et al, 2021). As movement lockdown and social distancing became the new norm in daily life, there was a significant reduction in students' activities, and this invariably impacted their quality of life (QoL) (Szczepanska & Pietrzyka, 2021).…”
Section: Introductionmentioning
confidence: 99%